Finding fault in a shear zone: A magnetic and drill core study in the Valentine Lake Property, Newfoundland, Canada - Flanagan, Marie; Leitch, Alison; Wall, Adam (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2023)
The Valentine Lake Property in southwestern Newfoundland has five known gold deposits over a distance of 20 km along a northeast to southwest trend and is expected to be the future site for the largest gold mine in Atlantic Canada. The property contains structurally controlled orogenic-type quartz-tourmaline-pyrite veins, which are gold-bearing, occurring along or proximal to the Valentine Lake Shear Zone. The mineralization is found mostly on the northwest side of the shear zone in intrusive rocks and is rare in the conglomerate on the southeast side. The area has many mafic dykes, which show up well when conducting a magnetic survey due to their magnetite content. These dykes, like the mineralization, occur mainly in the intrusive rocks and trend predominantly subparallel to the shear zone, and so can help indicate structure. To constrain the location of the shear zone (and hence the mineralized region) in an area where an offset was suspected, a detailed magnetic survey was conducted over a 200 m x 300 m grid comprising sixteen lines. With the collected data, residual magnetic intensity maps were created and processed. A region was identified where the pattern of linear magnetic highs weaken and appear to terminate near the suspected offset. In combination with drill core information, this location is interpreted as a fault offset of the shear zone. The loss in magnetic intensity is possibly due to alteration or thinning of the mafic dykes near the fault.